Legal Review On Auction Sales Of Mortgage Rights Object On Agricultural Land And Its Registration - Hardiansah Hardiansah; Amin Purnawan (Jurnal Akta, 2018)
Agrarian Law is one of the legal materials that are directly related to the livelihood of every individual society and the order of life of Indonesian society. The citizens until now are still very dependent on the activities and efforts that mostly work as agrarian, so that the land is one of Agrarian object which is the support and hope for every individual society in order to carry out a prosperous life order. The process of selling the land is divided into two ways: general sales and special sales by auction conducted by the State Property Office and Auction. This auction is conducted in the framework of repayment of debt secured by mortgage rights. This matter is regulated in Act No. 4 Of 1996 concerning Land Mortgage Rights and Objects Related to the Land and Regulation of Minister of Finance Number 27/PMK.06/2016 concerning Guideline for Auction Implementation of Auction or public sale is a part of the occurrence the transfer of rights. According to Article 41 paragraph (1) of Government Regulation No. 24 of 1997 concerning Land Registration explains that the transfer of rights through auction can only be registered if it is proven by quotation of auction minutes made by auction officials.Keywords: Auction Sales; Mortgage Right Objects; Land Registration.